Upaya Peningkatan Mobilitas Fisik Pada Pasien Stroke Dengan Hemiparese - Andriyani, Ari; , Dian Hudiyawati, S.Kep.,Ns., M.Kep (2017)
Background: According to the Central Java Provincial Health Office (2012), the prevalence of stroke in Central Java in 2012 was 0.07 higher than in 2011 (0.03%). Problems often arise in stroke patients is the occurrence of physical mobility disorder mainly occurs hemiplegia or hemiparese. Someone who experience movement disorders or disturbances in muscle strength will have an impact on daily activities. To increase muscle strength necessary mobilization exercises, which aim to improve neurological function and prevent contractures or stiffness of muscles with physical therapy and other techniques. Objective: To provide an overview of nursing care efforts to increase physical mobility in and to prevent muscle stiffness in patients with stroke. Methods: The method used is descriptive case studies in stroke patients conducted on the 10th until February 12th, 2017 covering five nursing process ranging from assessment, determine a diagnosis, intervention, implementation and evaluation. Data were obtained from medical records, observation, interview, physical examination and documentation of journals also books. Results: Patients showed increased physical mobility after give the nursing care. The effect of the action Range Of Motion (ROM) and reposition improve physical mobility. Conclusion: The issue is resolved physical mobility constraints partly because of the right limb was able to be moved, but not maximized. Thus require treatment or further mobilization exercises in order to achieve the expected outcomes.